Perancangan Alat Ukur Tingkat Kapabilitas Manajemen Perubahan SPBE Menggunakan Kerangka Kerja Cobit 5 - Shaharani Azpriyanne Cahyono; Siti Mukaromah; Anita Wulansari (Lembaga Pengembangan Kinerja Dosen, 2023)
Information technology (IT) is an important part used in everyday life. The application of information technology is an important aspect for companies or organizations because it will have an impact on increasing economic growth, national stability, and organizational welfare, or community welfare. XYZ Institution is one of the government agencies that seeks to realize good governance by utilizing information technology. In realizing the implementation of the Electronic Based Government System (SPBE), the implementation of change management has not been running perfectly, so that the implementation has not been carried out in a recorded manner and is not in accordance with the applicable SOPs. From the existing problems, this study aims to design a measuring instrument for calculating the level of IT capability of SPBE change management at XYZ Institutions based on the COBIT 5 with the selected domains BAI06 and BAI07. The results of this study produce a change management capability level measuring tool that is in accordance with the COBIT 5. With the preparation of this capability level measurement tool, it can produce recommendations based on calculations that have been carried out, so that it can be an improvement to encourage IT management efficiency in line with company goals